2023
DOI: 10.1002/anie.202311721
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Ta/Cu Architectures via Metal‐Metal Salt Metatheses: Heterobimetallic C−H Bond Activation Affords μ‐Hydrides

Michela L. Maiola,
Joshua A. Buss

Abstract: We employ a metal‐metal salt metathesis strategy to access low‐valent tantalum‐copper heterometallic architectures (Ta–µ2‐H2–Cu and Ta–µ3‐H2–Cu3) that emulate structural elements proposed for surface alloyed nanomaterials. Whereas cluster assembly with carbonylmetalates is well precedented, the use of the corresponding polyarene transition metal anions is underexplored, despite recognition of these highly reactive fragments as storable sources of atomic Mn–. Our application of this strategy provides structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 110 publications
0
1
0
Order By: Relevance
“…A search in the CCDC database for Ta−Cu species, where the two metal centers are separated by 2.7 Å or less revealed only one recent study from Buss and Maiola, who reported hydride-bridged species, in which the Ta−Cu distances span the range [2.61− 2.90 Å]. 90 The Ta−Cu distance in 2-Cu (2.7018(8) Å) is falling in this range, which is in between the sum of the respective metallic radii (Ta: 1.343 Å; Cu: 1.173 Å; sum = 2.516 Å) 91 and covalent radii (Ta: 1.70 Å; Cu: 1.32 Å; sum = 3.02 Å). 92 This provides a potential avenue for metal−metal interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search in the CCDC database for Ta−Cu species, where the two metal centers are separated by 2.7 Å or less revealed only one recent study from Buss and Maiola, who reported hydride-bridged species, in which the Ta−Cu distances span the range [2.61− 2.90 Å]. 90 The Ta−Cu distance in 2-Cu (2.7018(8) Å) is falling in this range, which is in between the sum of the respective metallic radii (Ta: 1.343 Å; Cu: 1.173 Å; sum = 2.516 Å) 91 and covalent radii (Ta: 1.70 Å; Cu: 1.32 Å; sum = 3.02 Å). 92 This provides a potential avenue for metal−metal interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Molecular compounds associating Ta and Cu are extremely rare in the literature, and to our knowledge, there is no structurally characterized tantalum/copper molecular complex featuring an unsupported metal–metal interaction (i.e., without bridging ligands) reported to date. A search in the CCDC database for Ta–Cu species, where the two metal centers are separated by 2.7 Å or less revealed only one recent study from Buss and Maiola, who reported hydride-bridged species, in which the Ta–Cu distances span the range [2.61–2.90 Å] . The Ta–Cu distance in 2-Cu (2.7018(8) Å) is falling in this range, which is in between the sum of the respective metallic radii (Ta: 1.343 Å; Cu: 1.173 Å; sum = 2.516 Å) and covalent radii (Ta: 1.70 Å; Cu: 1.32 Å; sum = 3.02 Å) .…”
Section: Resultsmentioning
confidence: 99%
“…10 ). 71 During the synthesis, bridging hydrides are incorporated in these heterometallic compounds. The origin of these hydrides was investigated by isotopic crossover experiments using either deuterated solvent (THF-d 8 or toluene-d 8 ) and deuterated naphtalenide.…”
Section: Early/late Transition Metal Systemsmentioning
confidence: 99%